2004
DOI: 10.1007/bf03324544
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy and blood pressure as predictors of cognitive decline in old age

Abstract: Results indicate that, the closer cognitive decline, the lower the BP, and suggest that, although LVH is a risk factor of cognitive decline, it loses its predictive value in old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 34 publications
3
45
1
2
Order By: Relevance
“…Although this observation is consistent with some prior work,9, 10 the remaining null cognitive results contrast with literature reporting cognitive associations with LVH8 or increased LV mass index3, 28 in aging cohorts that include dementia cases. Although increased LV mass index is an early marker of pathologic LV remodeling, it may not strongly correspond with subtle cognitive changes in cognitively normal individuals or elders with only mild prodromal symptoms of dementia, such as those participants studied here.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although this observation is consistent with some prior work,9, 10 the remaining null cognitive results contrast with literature reporting cognitive associations with LVH8 or increased LV mass index3, 28 in aging cohorts that include dementia cases. Although increased LV mass index is an early marker of pathologic LV remodeling, it may not strongly correspond with subtle cognitive changes in cognitively normal individuals or elders with only mild prodromal symptoms of dementia, such as those participants studied here.…”
Section: Discussionsupporting
confidence: 89%
“…Although increased LV mass index is an early marker of pathologic LV remodeling, it may not strongly correspond with subtle cognitive changes in cognitively normal individuals or elders with only mild prodromal symptoms of dementia, such as those participants studied here. Furthermore, prior work has shown that the association between increased LV mass index and cognition is attenuated when other cardiovascular risk factors are adjusted for,3, 8, 9, 10 as was done here with the inclusion of a vascular risk score.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These imaging markers of cSVD are strongly associated with cognitive function 3, 4, 5, 6. Other types of hypertensive organ damage, such as cardiac and renal damages, have also been linked to lower cognitive function or increased risk of cognitive impairment 7, 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%